Korean Maize Hybrids Present Significant Diversity in Fatty Acid Composition: An Investigation to Identify PUFA-Rich Hybrids for a Healthy Diet - Ramesh Kumar Saini; Kannan R. R. Rengasamy; Kannan R. R. Rengasamy; Kannan R. R. Rengasamy; Eun-Young Ko; Jung-Tae Kim; Young-Soo Keum (Frontiers in Nutrition, 2020)
Precise information on the content and composition of nutritionally essential metabolites in food crops is a prerequisite for dietary recommendations and nutrient-dense food formulations. In the present study, the fatty acid profile of 21 Korean maize hybrids was analyzed by gas chromatography (GC)–mass spectrometry (MS). In the studied hybrids, linoleic acid (LA; C18:2n6c) was dominant (38.0–58.9%), followed by oleic (OA; C18:1n9c) (23.5–45.3%), palmitic (C16:0) (10.8–17.3%), and stearic acids (C18:0) (1.84–3.86%). Among all the quantified fatty acids, the highest variation was recorded for LA and OA. The highest amount of LA (58.9%), the lowest amount of OA (23.5%), and the highest polyunsaturated fatty acids (PUFAs)/monounsaturated fatty acids (MUFAs) ratio of 2.47 were recorded in the Shingwang hybrid. The highest PUFAs/saturated fatty acids (SFAs) ratio of 4.04 was recorded in the Ahndaok hybrid due to the high content of LA (57.8%) and low amount of SFA. Similarly, the highest PUFAs + MUFAs/SFAs ratio of 6.38 was recorded in the Pyeonggangok hybrid as a result of the high OA (34.6%) and LA (51.4%) contents, along with the lowest amount of SFAs. Considering the high levels of health-beneficial MUFAs and PUFAs and low levels of undesirable SFAs, the maize hybrids Pyeonggangok, Ahndaok, and Shingwang can be used in the preparation of a healthy PUFA-rich diet.